Academic trajectories of generational groups and political context in Argentina: Towards a typology - Marquina, Monica; Yuni, José Alberto; Ferreiro, Mariela (Education Policy Analysis Archives, 2017)
Our aim is to analyze the trajectories of Argentinian academics through the study of three different groups: novel, intermediate and consolidated. For each group, we consider socio-cultural background, academic capital, elapsed time between graduation and the first academic position, type of activities carried out at present time, and level of satisfaction. Our hypothesis is the trajectories of each generational academic group correspond to the performative conditions of university policies at different socio-political moments. Hence, it is possible to distinguish types of trajectories, corroborating previous theoretical advances.